2017
DOI: 10.1002/hbm.23572
|View full text |Cite
|
Sign up to set email alerts
|

Genetic effect of MTHFR C677T polymorphism on the structural covariance network and white‐matter integrity in Alzheimer's disease

Abstract: The 677 C to T transition in the MTHFR gene is a genetic determinant for hyperhomocysteinemia. We investigated whether this polymorphism modulates gray matter (GM) structural covariance networks independently of white-matter integrity in patients with Alzheimer's disease (AD). GM structural covariance networks were constructed by 3D T1-magnetic resonance imaging and seed-based analysis. The patients were divided into two genotype groups: C homozygotes (n = 73) and T carriers (n = 62). Using diffusion tensor im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 62 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…To achieve SCN t-maps, we performed the general linear analysis on modulated GM images. Specifically, we extracted the GM volume from a 4-mm radius sphere (Montembeault et al, 2016; Chang et al, 2018; Chang et al, 2017) around those coordinates on modulated images. Then, we performed four separate correlation analysis by entering the GM volumes of each ROI as a regressor and the total intracranial volume, gender, age, and education as covariates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To achieve SCN t-maps, we performed the general linear analysis on modulated GM images. Specifically, we extracted the GM volume from a 4-mm radius sphere (Montembeault et al, 2016; Chang et al, 2018; Chang et al, 2017) around those coordinates on modulated images. Then, we performed four separate correlation analysis by entering the GM volumes of each ROI as a regressor and the total intracranial volume, gender, age, and education as covariates.…”
Section: Methodsmentioning
confidence: 99%
“…We set the threshold at P ≤ 0.01 corrected for false discovery rate (FDR). Considering the physiological meanings of the SCN clusters, we reported clusters showing cluster size >100 voxels (Chang et al, 2018; Chang et al, 2017). To achieve qualitative group-wise comparisons, we displayed the results on a standard brain template (ICBM152).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant polymorphism at the level of the MTHFR gene is C677T, which induces increased homocysteine concentrations and DNA hypomethylation. Furthermore, it has been shown to be associated with neural tube defects, white matter integrity in Alzheimer patients, venous thrombosis, colorectal cancer survival, breast cancer and leukemia [143,144,145,146,147,148,149]. Continuing on, the links between MTHFR polymorphisms and lung cancer have also been extensively studied.…”
Section: Vitaminsmentioning
confidence: 99%
“…N-5, N-10-methylenetetrahydrofolate reductase (MTHFR) is the rate limiting enzyme in the metabolism of Hcy. Studies have found that MTHFR has a certain correlation with cerebrovascular disease [1,2] and has a predictive value in ischemic stroke [25]. However, the relationship between MTHFR gene C677T polymorphism and WML is still unclear.…”
Section: Introductionmentioning
confidence: 99%